2018
DOI: 10.1017/s0031182018000367
|View full text |Cite
|
Sign up to set email alerts
|

The role of metalloproteases inLeishmaniaspecies infection in the New World: a systematic review

Abstract: This is a systematic review on the role of metalloproteases in the pathogenicity of the American tegumentary leishmaniasis (ATL) caused by New World Leishmania species. The review followed the PRISMA method, searching for articles in PubMed, EMBASE, LILACS and ISI Web of Science, by employing the following terms: 'leishmaniasis', 'cutaneous leishmaniasis', 'mucocutaneous leishmaniasis', 'diffuse cutaneous leishmaniasis', 'Leishmania' and 'metalloproteases'. GP63 of New World Leishmania species is a parasite me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Thus, the ciliates must be able to resist the attack from the fish immune system and also to destroy fish tissue, for which proteases may be important. In the present study, we observed an increase in the expression of several genes of the leishmanolysin family, which are membrane-bound metalloproteases capable of degrading and cleaving many biological molecules [ 39 ]. Leishmanolysin GP63 is a major surface protein and is considered one of the main virulence factors in the human pathogen Leishmania [ 40 ].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the ciliates must be able to resist the attack from the fish immune system and also to destroy fish tissue, for which proteases may be important. In the present study, we observed an increase in the expression of several genes of the leishmanolysin family, which are membrane-bound metalloproteases capable of degrading and cleaving many biological molecules [ 39 ]. Leishmanolysin GP63 is a major surface protein and is considered one of the main virulence factors in the human pathogen Leishmania [ 40 ].…”
Section: Discussionmentioning
confidence: 95%
“…MSP proteins are known to play important roles in parasite virulence and in the pathogenesis of infections caused by Kinetoplastida [43]. In Leishmania spp., the MSP is called GP63 (63 kDa glycoprotein), a class of zinc metalloproteases abundant on the surface of the parasite, and one of the enzymes best studied and characterized in this parasite [44].…”
Section: Major Surface Proteases From Trypanosoma Brucei: An Impormentioning
confidence: 99%
“…In general, T. brucei metalloprotease is responsible for the degradation of proteins of the blood–brain barrier, such as collagen and laminin, which is possibly pivotal at the transition phase and hemolymphatic phase, to meningoencephalitis [53]. When the expression of the GPI–PLC enzyme in the procyclic forms of T. brucei occurs, the release of VSG is ensured by the constant expression of the MSP enzyme [20,44].…”
Section: Contribution Of the Plc Enzyme In The Removal Of Vsg On Tmentioning
confidence: 99%
“…The degree of pathogen or tissue leukocyte-driven proteolytic cleavage will regulate the degree of degradation vs. liberation of cleaved CCL7 with antagonist activity (16, 18). Indeed, the Leishmania metalloprotease GP63 is an extensively studied parasite virulence factor (60) and could directly alter chemokine activity. Competition between chemokines in the milieu for binding chemokine receptors and/or glycosaminoglycans (GAGs) may also regulate net chemotactic activity in the infected tissue.…”
Section: Discussionmentioning
confidence: 99%